Evaluation of Aerosol Therapy during the Escalation of Care in a Model of Adult Cystic Fibrosis - Elena Fernández Fernández; Mary Joyce; Andrew O'Sullivan; Ronan MacLoughlin (MDPI AG, 2021)
Lung disease is the main cause of morbidity and mortality in cystic fibrosis (CF). CF patients inhale antibiotics regularly as treatment against persistent bacterial infections. The goal of this study was to investigate the effect of clinical intervention on aerosol therapy during the escalation of care using a bench model of adult CF. Droplet size analysis of selected antibiotics was completed in tandem with the delivered aerosol dose (% of total dose) assessments in simulations of various interventions providing oxygen supplementation or ventilatory support. Results highlight the variability of aerosolised dose delivery. In the homecare setting, the vibrating mesh nebuliser (VMN) delivered significantly more than the jet nebuliser (JN) (16.15 ± 0.86% versus 6.51 ± 2.15%). In the hospital setting, using VMN only, significant variability was seen across clinical interventions. In the emergency department, VMN plus mouthpiece (no supplemental oxygen) was seen to deliver (29.02 ± 1.41%) versus low flow nasal therapy (10 L per minute (LPM) oxygen) (1.81 ± 0.47%) and high flow nasal therapy (50 LPM oxygen) (3.36 ± 0.34%). In the ward/intensive care unit, non-invasive ventilation recorded 19.02 ± 0.28%, versus 22.64 ± 1.88% of the dose delivered during invasive mechanical ventilation. These results will have application in the design of intervention-appropriate aerosol therapy strategies and will be of use to researchers developing new therapeutics for application in cystic fibrosis and beyond.